SYSTEM AND METHOD FOR MEASUREMENT OF CARDIORESPIRATORY FITNESS OF A SUBJECT - QUESTEL, Philippe; RABINEAU, Jérémy; MIGEOTTE, Pierre-François; HOSSEIN, Amin (2025)
Provided is a system (100) for determining a cardiorespiratory fitness measurement of a subject (50), comprising a processing unit (160), the processing unit (160) configured to: receive a stream of signals (120) outputted by a sensor unit (110) comprising one or more motion sensing modules (111), MSMs; determine, from the signal stream (120), a kinetic energy data stream, KEDS, for each non-exercise period (N) of an exercise session (E) for gradually increasing the oxygen consumption, VO2, of the subject, wherein the exercise session (E) comprises a plurality of alternating exertion segments (S) and non-exercise periods (N); for each non-exercise period (N): obtain a mean kinetic energy, MKE, that is a time-averaged kinetic energy value from a time window (W) of the kinetic energy data stream, KEDS; determine a period of mean kinetic energies, PMKEs, containing multiple MKEs for different time windows (W) within the non-exercise period (N); determine, from a set of PMKEs, SPMKE, containing multiple PMKEs within the exercise period (E), the cardiorespiratory fitness measurement of the subject.